Cronofarmacología en el tratamiento de la enfermedad por reflujo gastroesofágico. una revisión integradora - Quinga Acosta, Jefferson Abel (2025)
Chronopharmacology is a current study area related to the use of medications that significantly alter some of the "truths" previously taken for granted in pharmacological therapy. Gastroesophageal reflux disease (GERD) can be defined as a condition with sufficiently troublesome symptoms to affect an individuals quality of life, or as lesions or complications caused by the backward flow of gastric contents into the esophagus, oropharynx, and/or airways. This article emphasizes how biological rhythms can influence the response to medications and therapy (Chronopharmacology and chronotherapy). Therefore, the objective of the study is to integrate information about Chronopharmacology in the treatment of Gastroesophageal Reflux Disease to present a different perspective on the therapeutic approach to this disease. The methodology was based on qualitative research focused on analyzing information from various bibliographic studies in an effective and comprehensible manner, considering that this is an empirical-level article. The results of the study effectively compiled information to guide the correct dosage and administration of medications in order to control and prevent posible complications. It is concluded that advances in the study of biological rhythms have made it possible to establish first-line treatments to manage the disease differently, showing positive benefits when treatment follows the body’s internal biological rhythms, with better tolerability options.